Pre-treatment tumor-specific growth rate as a temporal biomarker that predicts treatment failure and improves risk stratification for oropharyngeal cancer. Issue 11 (November 2015) - Murphy, Colin T.; Devarajan, Karthik; Wang, Lora S.; Mehra, Ranee; Ridge, John A.; Fundakowski, Christopher; Galloway, Thomas J.
<x xml:space="preserve">Abstract</x> Highlights Serial imaging permits estimates of tumor-specific growth rate (TSGR) for OPC. Faster TSGR correlates well with p16 status, T-stage and smoking. TSGR predicts outcomes for oropharyngeal cancer (OPC) in the HPV era. TSGR calculation may improve identification of de-escalation candidates.